EDIBLE OFFAL OF BROILER SUBMITTED A COMMERCIAL RATION WITH ADDITIONALSTARBIO PROBIOTIC - I G., Novandy S. S.; Ariana, I N. T.; Wijana, I W. (Jurnal Peternakan Tropika, 2018)
The purpose of this research was to study the effect of  starbio probiotics added in commercial ration on edible offal of broiler. The research was conducted over 5 week in Mr. Ir. I Wayan Sana’s broiler farm.  The treatment that given is ST (0,25% starbio probiotics added in commercial ration) and NS (0% probiotics added in commercial ration).  Variables which were research is production of broiler that is initial final body weight, carcass percentage, digestive tract percentage, heart and liver percentage, shank percentage, legund percentage, chicken head percentage, and abdomen fat percentage. Data in this research were analyzed using of Two Independent Sampel T-test . he results showed that the addition of probiotic starbio 0,25% in commercial rations can reduce the weight of the cut but increase the percentage of carcasses from broiler chickens. Addition of 0,25% starbio probiotic in commercial ration has no effect on percentage of gastrointestinal tract, percentage of heart and liver, percentage of neck, percentage of head, percentage of claw, and percentage of abdominal fat. The results showed that the addition of probiotic starbio 0.25% in commercial rations can reduce the final body weightand abdomen fat percentage but increase the percentage of carcasses from broilers. Addition of 0.25% starbio probiotic in commercial ration has non significan on digestive tract percentage, heart and liver percentage, shank percentage, legund percentage, and chicken head percentage. Keywords : Probiotics, Starbio, Commercial Ration, Fat, Edible Offal, Broiler